ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN TABANAN - Evicahyani, Sagung Inten; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.03.TAHUN 2016, 2016)
Accountability is a form of accountability obligations success or failure of the mission of the organization in achieving its goals and objectives that have been set previously. Form of government accountability to the public in the form of financial statements. This research aims to analyze the influence of independent variables (Competence of Human Resources/SDM, Implementation of Government Accounting Standards/SAP, and Utilization of Regional Financial Information System/SIPKD, the dependent variable is quality of Local Government Finance Report/LKPD with intervening variables Implementation of Government Internal Control System/SPIPthrough SEM analysis approach Partial Least Square (PLS) aims analyze effect of independent variables (Competence of Human Resources, Implementation of Government Accounting Standards , and Utilization of Regional Financial Information System) on dependent variables ( quality of Local Government Finance Report )with variable intervening ( Implementation of Government Internal Control System ) by analysis Structural Aquation Modeling ( SEM ) PLS (partial least square) approach. Type of data uses in this research is primary data. Data used in this research is the primary data. Data collected through questionnaires to Financial Management (User Administration Budget and Finance Officer) on the Work Unit (SKPD) in Tabanan regency government. SKPDs number of 40 with each second respondent in the sector departments so that the total sample of 80 people. Result of Hypothesis testing indicates have an effect positive and significant the competence of Human Resources, Government Accounting Standards Implementation, Utilization of Financial Management Information System and significant positive effect, to the quality of Local Government Finance Report Tabanan either directly or indirectly through intervening variables, namely the adoption of Government Internal Control System.
Keywords: SDM, SAP, SIPKD, SPIP, LKPD